(untitled) (Gestão & Regionalidade, 2021)
Despite the relevant number of studies relating entrepreneurship to spatial and territorial aspects, research on cultural entrepreneurship in relation to these issues is unknown. In the context of cultural and creative economies, sustained and energized by entrepreneurial forces, wouldn’t thinking about their relationship with territorial and spatial aspects be a way to make development more rooted, political, distinctive, and robust? As such, this theoretical-conceptual systematic review is based on literature about entrepreneurship, cultural entrepreneurship and territoriality. The purpose is to presents and discuss perspectives and challenges for a territorial conceptualization of cultural entrepreneurship. The results provide (a) an integrated view of how territorial concepts are used in the field of entrepreneurship, (b) spatial perspectives for reorienting further research on cultural entrepreneurship, and (c) a discussion of this reorientation